2014
DOI: 10.1002/jsfa.7024
|View full text |Cite
|
Sign up to set email alerts
|

CERES‐Maize model‐based simulation of climate change impacts on maize yields and potential adaptive measures in Heilongjiang Province, China

Abstract: BACKGROUND: Climate change would cause negative impacts on future agricultural production and food security. Adaptive measures should be taken to mitigate the adverse effects. The objectives of this study were to simulate the potential effects of climate change on maize yields in Heilongjiang Province and to evaluate two selected typical household-level autonomous adaptive measures (cultivar changes and planting time adjustments) for mitigating the risks of climate change based on the CERES-Maize model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
3
30
0
3
Order By: Relevance
“…Constantin et al [17] with AqYield and STICs models, reported NRMSE of 15% and 18% respectively. Using CERES-Maize, Lin et al referred NRMSE near 11% [18], and Ma et al [69] reported NRMSE ranging 6% to 12% and 5% to 7% when using, respectively, the DSAAT-CERES and the RZWQ-CERES models. Ko et al [70] reported RMSE of 0.5 and 0.87 t¨ha´1 but representing NRMSE of 7% and 11% of the average observed yields.…”
Section: Water-yield Relations and Yield Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constantin et al [17] with AqYield and STICs models, reported NRMSE of 15% and 18% respectively. Using CERES-Maize, Lin et al referred NRMSE near 11% [18], and Ma et al [69] reported NRMSE ranging 6% to 12% and 5% to 7% when using, respectively, the DSAAT-CERES and the RZWQ-CERES models. Ko et al [70] reported RMSE of 0.5 and 0.87 t¨ha´1 but representing NRMSE of 7% and 11% of the average observed yields.…”
Section: Water-yield Relations and Yield Predictionsmentioning
confidence: 99%
“…These include water-yield functions and crop growth and yield models. Applications of crop yield models to maize are numerous (e.g., [15][16][17][18]). However, these models are very demanding in terms of data and parameterization and may not be better than adopting a combination of a water balance simulation model with a water-yield function.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also obtained by Challinor et al and Simelton et al Hence, the use of different sowing dates as an adaptation approach found that delaying the sowing date will be advantageous in order to mitigate the adverse effects of climate change by avoiding thermal stress at the growth period and obtain higher yield in all of the study areas in next decades. There are many studies which have focused on the efficiency of agronomic adaptation and mitigation approaches in relation to climate‐induced yield losses in different locations …”
Section: Discussionmentioning
confidence: 99%
“…Results of many studies suggested that the impacts of climate change without using adaptation and mitigation strategies may create considerable problems related to agricultural production and economies . On the other hand, various studies have been conducted to investigate the role of the agronomic mitigation or adaptation strategies to climate change . However, it should be noted that the efficacy of adaptation and mitigation strategies in each region is different and no single approach can give the required information for adapting agriculture in a changing climate, hence it is possible to use the vulnerability index to identify which areas and/or years have higher or lower response to these strategies and which adaptation and mitigation efforts are likely to be most effective and thus how one may prioritise them .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the duration of reproductive phases in maize from emergence to flowering and physiological maturity would be shortened under future climate change, and yield would reduce by 11 to 46% from 2011 to 2099 relative to 1981 to 2010 (Lin et al, 2015). Additionally, maize production would not benefit significantly from increased CO 2 fertilization.…”
Section: Impact Of Climate Change On Maize Yield Using Dssat Ceres-mamentioning
confidence: 99%